Interaction Effect of Process Variables on Solar-Assisted Photocatalytic Phenol Degradation in Oilfield Produced Water Over ZnO/Fe2O3 Nanocomposites - Al Haiqi, Omer; Nour, A. H.; Ayodele, Bamidele Victor; Bargaa, Rushdi (Akademi Baru, 2020)
This study investigates the interaction effects of process variables on photocatalytic phenol degradation in oil produce water. A series of ZnO/Fe2O3 nanocomposite prepared using the sol-gel method and calcined at a temperature range of 400-600 oC were employed as photocatalysts. The characterization analysis using different instrument techniques revealed that the ZnO/Fe2O3 nanocomposites have suitable physicochemical properties as photocatalysts. The photocatalytic activity of the ZnO/Fe2O3 nanocomposite was examined in photo-reactor considering the degradation of the phenol and the reduction in chemical oxygen demand (COD) in the oilfield produced water under direct sunlight. It was ascertained that process variables such as irradiation time, calcination temperature of the ZnO/Fe2O3 nanocomposites, and the ZnO/Fe2O3 nanocomposites concentration significantly influenced the chemical oxygen demand and phenol removal. Based on the analysis of variance (ANOVA), the effects of the process variables on the phenol and COD removal can be ranked as irradiation time (p-value < 0.0001) > calcination temperature of the ZnO/Fe2O3 nanocomposite (p-value = 0.0003) > ZnO/Fe2O3 concentration (p-value = 0.0013). The interaction between the parameters was observed to have a substantial effect on COD and phenol removal. However, the interaction effect that produced the most significant influence on the COD and phenol removal was recorded between the irradiation time and the ZnO/Fe2O3 nanocomposite concentration.